Integrations of Nation Beyond the Maritime Borders: Effort and Experience Malaysia In Strengthening and Developing Relationships with Indonesia - Mohd bin Samsudin (Journal of Maritime Studies and National Integration, 2019)
Malaysia inherited the legacy of the famous maritime empire of Srivijaya and Malacca Sultanate. Before western imperialism come, the Malay community in the region, especially in the Strait of Malacca enjoy a close relationship, regardless of borders. Historical experience binds the role and importance of maritime as a priority in realizing the relations between the people of Malaysia and Indonesia before the independence of the two countries which established inter-community interdependence. In fact, this interdependence that has enriched people's lives in economics and culture. Western colonialism had broken the ties of society when the borders were set up by them. But after the two countries became independent, there was an effort to re-establish a relationship based on historical and cultural experiences. Despite the experience of love and sorrow, the fact is that the priority to strengthen relations with Indonesia has never been forgotten by Malaysian leaders. Various efforts have been made in the field of economic, social,and cultural cooperation including IMT-GT. Communication and cultural cooperation between the two countries. The economic difficulties encountered during the financial crisis of the late 1990s, by sharing common experiences have strengthened leaders' confidence to prioritize intergenerational integration. Using the Collective Memory method, this paper will examinehistorical and cultural experiences as the basis for closer relationships. Furthermore, it will discuss Malaysia's efforts to strengthen and prosper the people of both countries through various means, especially ASEAN, IMT-GT economic development cooperation, SIJORI, inter-governmental cooperation, and inter-community cooperation that took place during Prime Minister Tun Abdul Razak's leadership and Tun Dr. Mahathir Mohamad.